Graphene and its Derivatives for Bone Tissue Engineering: In Vitro and In Vivo Evaluation of Graphene-Based Scaffolds, Membranes and Coatings - Cheng, Junyao; Liu, Jianheng; Wu, Bing; Liu, Zhongyang; Li, Ming; Wang, Xing; Tang, Peifu; Wang, Zheng (Frontiers in Bioengineering and Biotechnology, 2021)
Bone regeneration or replacement has been proved to be one of the most effective methods available for the treatment of bone defects caused by different musculoskeletal disorders. However, the great contradiction between the large demand for clinical therapies and the insufficiency and deficiency of natural bone grafts has led to an urgent need for the development of synthetic bone graft substitutes. Bone tissue engineering has shown great potential in the construction of desired bone grafts, despite the many challenges that remain to be faced before safe and reliable clinical applications can be achieved. Graphene, with outstanding physical, chemical and biological properties, is considered a highly promising material for ideal bone regeneration and have attracted broad attention. In this review, we provide an introduction to the properties of graphene and its derivatives. In addition, based on the analysis of bone regeneration processes, interesting findings of graphene-based materials in bone regenerative medicine are analyzed, with special emphasis on their applications as scaffolds, membranes, and coatings in bone tissue engineering. Finally, the advantages, challenges, and future prospects of their application in bone regenerative medicine are discussed.